Research on Digital Transformation of Hospital Finance Based on "Big Data + Cloud Platform - Wan, Dongqi; Guo, Zhongpei (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: This study examines how the Big Data and Cloud Platform (BD+CP) architecture enhances accounting efficiency in public hospitals by integrating business and financial processes to achieve sustainable competitiveness. Methodology/Approach: Adopting a qualitative–analytical design, the research synthesizes secondary evidence (2019–2025), policy documents, and empirical case studies to construct a tripartite BD+CP implementation framework through document analysis, policy comparison, and conceptual system modeling. Originality/Relevance: The study bridges fragmented literature on technology, process, and governance by presenting a unified BD+CP model aligned with China’s 2021–2030 healthcare digitalization agenda. Key Findings: BD+CP adoption led to 75% faster transactions, 81% less redundancy, and 99.2% audit completion, with real-time data access rising from 18% to 94%. Theoretical/Methodological Contributions: The research introduces a replicable framework linking Digital Capability, Financial Sustainability, and Organizational Intelligence, reframing hospital finance as a proactive, strategic governance system.